Urban environment and mental health: the NAMED project, protocol for a mixed-method study. Issue 2 (20th February 2020) - Lauwers, Laura; Trabelsi, Sonia; Pelgrims, Ingrid; Bastiaens, Hilde; De Clercq, Eva; Guilbert, Ariane; Guyot, Madeleine; Leone, Michael; Nawrot, Tim; Van Nieuwenhuyse, An; Remmen, Roy; Saenen, Nelly; et al.
Abstract : Introduction: Mental health issues appear as a growing problem in modern societies and tend to be more frequent in big cities. Where increased evidence exists for positive links between nature and mental health, associations between urban environment characteristics and mental health are still not well understood. These associations are highly complex and require an interdisciplinary and integrated research approach to cover the broad range of mitigating factors. This article presents the study protocol of a project called Nature Impact on Mental Health Distribution that aims to generate a comprehensive understanding of associations between mental health and the urban residential environment. Methods and analysis: Following a mixed-method approach, this project combines quantitative and qualitative research. In the quantitative part, we analyse among the Brussels urban population associations between the urban residential environment and mental health, taking respondents' socioeconomic status and physical health into account. Mental health is determined by the mental health indicators in the national Health Interview Survey (HIS). The urban residential environment is described by subjective indicators for the participant's dwelling and neighbourhood present in the HIS and objective indicators for buildings, network infrastructure and green environment developed for the purpose of this project. We assess the mediating role of physical activity, social life, noise and air pollution. In the qualitative part, we conduct walking interviews with Brussels residents to record their subjective well-being in association with their neighbourhood. In the validation part, results from these two approaches are triangulated and evaluated through interviews and focus groups with stakeholders of healthcare and urban planning sectors. Ethics and dissemination: The Privacy Commission of Belgium and ethical committee from University Hospital of Antwerp respectively approved quantitative database merging and qualitative interviewing. We will share project results with a wide audience including the scientific community, policy authorities and civil society through scientific and non-expert communication.